DIGITAL ACADEMIC ENTREPRENEURSHIP: NEW OPPORTUNITIES FOR STUDENTS IN THE DEVELOPMENT OF THE INFORMATION ENVIRONMENT - Goncharov, Vitaly; Sekerin, Vladimir; Akhyadov, Elman (Revista Inclusiones, 2020)
Purpose of the article. The purpose of the research is to analyze the opportunities of digital academic entrepreneurship provided to students in the context of the development of the information environment. Main results. To develop digital academic entrepreneurship, it is necessary to combine all available resources (human, organizational, financial) of existing research parks and departments for the development and support of entrepreneurship, create "exemplary" successful spin-off projects (subsidiaries created by employees or alumni of a university, based on technologies, the rights to which belong to the university), train students in entrepreneurial skills, and "unlock" scientific knowledge by institutions that are unable to ensure the practical use of their patents. Application of the study. The results of the work can be used in the organization of academic entrepreneurship at universities. The materials and conclusions of the study can be used in teaching the subjects of the business cycle in higher education.